Supergirl - Szwarc, Jeannot, 1939-; Dunaway, Faye, 1941-; Helen Slater; Peter O'Toole; Mia Farrow; Brenda Vaccaro; Peter Cook; Simon Ward; Marc McClure; Hart Bochner; Maureen Teefy; David Healy; et al. (UK Artistry Limited, 1984)
Supergirl heads to earth to recover the Omegaheadron, which is the power source for her home world. The Omegaheadron falls into the hands of a second rate witch named Selena who uses it to try to take over the world. A silly subplot rears its ugly head when Selena uses a spell to make a gardener fall in love with her but he instead falls for Supergirl who now goes by the name of Linda Lee. Supergirl must now stop Selena and save the gardener.
Supergirl is transported to Earth accidentally, where she meets Ethan. Ethan has been put under a spell by the witch Selena, which makes him fall in love with the first person he sees. When the spell causes Ethan to fall in love with Supergirl and not Selena, the witch is furious and calls upon the forces of evil to fight Supergirl.
Introducing a brand new superhero--the beautiful and mighty Girl of Steel in her very first adventure. Her name is Kara, and she's Superman's cousin from Krypton. Coming to Earth on a mission to save her dying city, Supergirl has to find and recover the Omegahedron, a source of almost unlimited power. But it's fallen into the hands of an amateur witch named Selena--who intends to use it to rule the world! To get it back, Supergirl has to fight not only evil humans, but the unimaginable forces of Black Magic (including a hundred-foot monster made of pure energy), and make a perilous journey into the forbidden depths of the Phantom Zone.
Her first great adventure.
Languages : English, German, French, Spanish, Italian Subtitle : English
Keywords: SciFi; Adventure; Fantasy; Action